Effect of freeze-thaw cycles on static properties of cement stabilised subgrade silty soil. Issue 11 (19th September 2022) - Liu, Han-bing; Sun, Shuang; Wei, Hai-bin; Li, Wen-jun
ABSTRACT: Silty soil as a rich reserved subgrade fills in seasonally frozen regions of northern China, experienced at least one freeze-thaw (F-T) cycle each year. Many damages will occur after F-T cycles. In general, using cement to stabilise can alleviate that situation. Hence, a series of unconsolidated and undrained triaxial compression tests were conducted to evaluate the static properties (i.e. cohesion, internal friction angle, shear strength, stress–strain curves and resilient modulus) of cement stabilised silty soil. Meanwhile, the analysis of variance method was adopted to analyse the effects of multiple factors i.e. F-T cycles, confining pressures, water content and cement content on the resilient modulus. The results showed that the cohesion, shear strength and resilient modulus decreased with F-T cycles and water content, while increased with cement content, and tended to be stable after six cycles. The internal friction angle increased with cement content, whereas had no obvious regularities with F-T cycles and water content. The inclusion of cement could transform the stress–strain curves from strain hardening to strain softening, and inhibited the negative impact of F-T cycles and water content on resilient modulus. Based on the above analysis, w opt, 2% cement content and the mechanical property index after six F-T cycles could be used as guidance for actual projects. Moreover, an empirical equation for determining the resilient modulus was proposed and validated.